Magnetic susceptibility record of loess/paleosol sequence: Case study from south-west Slovakia - ĎURŽA, Ondrej; DLAPA, Pavel (Contributions to Geophysics and Geodesy, 2009)
The paper proposes a new method to distinguish between paleosols and glacial loess deposits. The aim of our study is to test whether magnetic susceptibility measure- ments can be used as proxies for determining the boundary between the loess and paleosol. The measurements show excellent correlation with occurrence of the horizons inﬂuenced with pedogenesis. These values are generally explained in terms of the greater concentra- tions of ultraﬁne ferrimagnetic minerals in the recent soils and paleosols. The observed relationship between the susceptibility and lithology follows the behavior observed on the Chinese Loess Plateau, which is the complete opposite of the pattern reported from Alaskan and Siberian loess deposits.